The Influence of Social Media on the Decision to Visit Gulamo Tourist Attractions in Kampar Regency - M. Firdaus Alfarizi; Violintikha Harmawan (Journal of Multidimensional Management, 2025)
This study examines the influence of social media on tourists’ decisions to visit the Gulamo Tourist Attraction in Kampar Regency, Indonesia. Using a quantitative, causal-associative approach, data were collected from 100 respondents through structured questionnaires. Descriptive analysis revealed high perceptions of social media’s role in shaping travel behavior, particularly across five dimensions: ease of use, interactivity, entertainment, communication effectiveness, and content credibility. Inferential analysis through simple linear regression confirmed a statistically significant relationship (β = 0.682, p < 0.001), with social media explaining 65.2% of the variance in visit decisions (R² = 0.652). The findings underscore the strategic role of user-generated content and digital engagement in influencing destination choice, especially in under-promoted ecotourism sites. The study contributes to tourism marketing literature by highlighting how social media acts as an effective tool in behavioral persuasion and travel decision-making processes